A new species of Gentiana (Gentianaceae) for western Mexico - Villarreal Q., Jose A. (Instituto de Ecología, A.C., 1996)
Gentiana durangensis Villarreal is described as a new species of the section Pneumonanthe from western Mexico. Related to G. hooperi by its similar habit and usually 3 to 4 flowers per stem, and to G. bicuspidata by its similar habit and corolla shape, it differs from the latter by commonly having more than one flower, and from both by the herbaceous leaves, a truncate and minutely lobed calyx, and a not deeply incised corolla with much more broadly rounded, almost truncate lobes.